The Use of Myocardial Performance Index (Mpi) in Assessment of Heart Function - Saeed, Basil N.; Salim, F.; ALsaynee, M-; ALsaynee, M-; Sunbul, L.- (AL-Kindy College Medical Journal, 2009)
Background: Ejection fraction have been used frequentlyfor assessment of the left ventricular function, but can beassociated with errors in which myocardial performanceindex have been used as another parameter to measure theleft ventricular function.Objective: selecting another echocardiography parameterfor the assessment of myocardial in function instead of theejection fraction.Methods: 160 patients referred to the echocardiogram unitfrom the period december 2007 to august 2008 requestingassessment of left ventricular function. After clinicalexamination, routine blood tests; chest x-ray andelectrocardiographic recording have been completed. Allpatients informed to come for this unit after the first visitmonthly for three successive months. For the purpose ofcomparison (30) thirty volunteers admitted to this study ascontrol having same age range. The (160) patients werecategorized into two groups.Group (A) includes (70) patients with ischemic heartdisease with complications like pulmonary oedema,myocardial infarction, recent admission to coronary careunit because of recurrent severs chest pain. Group (B)includes (90) patients with ischemic heart disease withoutany of the above complications. Myocardial performanceindex is done by using the four chambers view and pulsewave and curser along the mitral inflow of the blood jet.Results: Assessment of left ventricular function by usingthe myocardial performance index in group A was moresignificant than using the ejection fraction in comparison tothe control group (P value 0.02, 0.03 respectively) the samewas found in group B in comparison to control group (Pvalue 0.01; 0.05 respectively).Conclusion The myocardial performance index (MPI) inthe control groups was 0.44-0.36 MS indicating that itsrange is very narrow in the control group, The (MPI) in thetwo groups of patients was high in comparisons withcontrol group